Part of the global DOC versus AOU (dissolved organic carbon/apparent oxygen utilization) data compilation, Indian Ocean - Doval, María Dolores; Hansell, Dennis A (PANGAEA, 2000)
Samples for total organic carbon (TOC) analysis were collected on WOCE Line P15S (0° to 67°S along 170°W) and from 53° to 67°S along 170°E in the western South Pacific, and on Line I8 (5°N to 43°S along 80°/90°E) in the central Indian Ocean. TOC concentrations in the upper ocean varied greatly between the regions studied. Highest surface TOC concentrations (81-85 µM C and 68-73 µM C) were observed in the warmest waters (>27°C) of the western South Pacific and central Indian Oceans, respectively. Lowest surface TOC concentrations (45-65 µM C) were recorded in the southernmost waters occupied (>50°S along 170°W and 170°E). Deep water (>1000 m) TOC concentrations were uniform across all regions analyzed, averaging between 42.3 and 43 µM C (SD: ±0.9 µM C). Mixing between TOC-rich surface waters and TOC-poor deep waters was indicated by the strong correlations between TOC and temperature (r2>0.80, north of 45°S) and TOC and density (r2>0.50, southernmost regions). TOC was inversely correlated with apparent oxygen utilization (AOU) along isopycnal surfaces north of the Polar Frontal Zone (PFZ) and at depths <500 m. The TOC:AOU molar ratios at densities of sigmaT 23-27 ranged from -0.15 to -0.34 in the South Pacific and from -0.13 to -0.31 in the Indian Ocean. These ratios indicate that TOC oxidation was responsible for 21%-47% and 18%-43% of oxygen consumption in the upper South Pacific and Indian Oceans, respectively. At greater depths, TOC did not contribute to the development of AOU. There was no evidence for significant export of dissolved and suspended organic carbon along isopycnal surfaces that ventilate near the PFZ.
Supplement to: Doval, María Dolores; Hansell, Dennis A (2000): Organic carbon and apparent oxygen utilisation in the western South Pacific and the central Indian Oceans. Marine Chemistry, 68(3), 249-264
Keywords: Joint Global Ocean Flux Study (JGOFS)